THE INFLUENCE OF MUSIC-BASED LEARNING ON VOCABULARY RETENTION IN EFL STUDENTS (SCIENCE TIME JOURNAL, 2026)
Learning a new language can be both exciting and challenging, especially for young EFL students striving to expand their vocabulary. This study explores how music-based learning can transform the language acquisition process, making it not only effective but also deeply engaging. By integrating songs and rhythmic exercises into lessons, students showed remarkable improvement inremembering new words, demonstrating that music has the power to connect emotion and cognition.Beyond academic gains, the experience boosted learners’ confidence and enjoyment, creating a positive environment where curiosity and creativity thrive. The findings suggest that when education resonates with the heart as well as the mind, vocabulary retention becmes more natural, lasting, and meaningful. Additionally when vocabulary is acquired with interactive musical methods, students learn how to use them actively, thereby improving their fluency. This research underscores the potential of music as a bridge between language learning and emotional engagement, highlighting a path toward more inspiring and human-centered classrooms.